2003
DOI: 10.1097/01.asn.0000100127.54107.57
|View full text |Cite
|
Sign up to set email alerts
|

Association of Comorbid Conditions and Mortality in Hemodialysis Patients in Europe, Japan, and the United States

Abstract: Abstract. Mortality rates among hemodialysis patients vary greatly across regions. Representative databases containing extensive profiles of patient characteristics and outcomes are lacking. The Dialysis Outcomes and Practice Patterns Study (DOPPS) is a prospective, observational study of representative samples of hemodialysis patients in France, Germany, Italy, Japan, Spain, the United Kingdom, and the United States (US) that captures extensive data relating to patient characteristics, prescriptions, laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
500
13
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 696 publications
(559 citation statements)
references
References 17 publications
28
500
13
14
Order By: Relevance
“…1,3 The prevalence of case-mix characteristics was determined by examining records from an international cross-sectional cohort of 8,615 patients. Mortality was recorded for this inception cohort, plus replacement patients, for a total of 16,720 patients, from 1996 through 2002.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3 The prevalence of case-mix characteristics was determined by examining records from an international cross-sectional cohort of 8,615 patients. Mortality was recorded for this inception cohort, plus replacement patients, for a total of 16,720 patients, from 1996 through 2002.…”
Section: Methodsmentioning
confidence: 99%
“…5 The case definitions for the other comorbid diseases are delineated in the appendix to the original comorbidities report. 3 Hepatitis B seroconversion was defined as documented change from negative HBV surface antigen status at entry to positive while on study. Similarly, patients who were HCV antibody negative at study entry and subsequently found to be HCV antibody positive were defined as cases of HCV seroconversion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results seems worthy of consideration with regard to the application of our results to other populations. First, it is well known that one of the features of hemodialysis patients in Japan is longevity (45); however, changes in mortality rates had little impact on the ICER as shown in Figure 3. Differences in underlying primary kidney disease may also affect the incidences of CVD, fracture, and death, but changes in these incidence rates had little impact on the ICER in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Care of CKD patients, especially for dialysis patients, has been traditionally quite intensive in Japan, which could have potentially contributed to the much better prognosis than other countries [12]. Achievement of strict target range of mineral parameters by Japanese guidelines [13,14], especially focused on phosphorus [15,16], may in part explain such a better prognosis [17].…”
mentioning
confidence: 99%